RRMdb—an evolutionary-oriented database of RNA recognition motif sequences. (16th January 2019) - Nowacka, Martyna; Boccaletto, Pietro; Jankowska, Elzbieta; Jarzynka, Tomasz; Bujnicki, Janusz M; Dunin-Horkawicz, Stanislaw
Abstract: RNA-recognition motif (RRM) is an RNA-interacting protein domain that plays an important role in the processes of RNA metabolism such as the splicing, editing, export, degradation, and regulation of translation. Here, we present the RNA-recognition motif database (RRMdb), which affords rapid identification and annotation of RRM domains in a given protein sequence. The RRMdb database is compiled from 57 000 collected representative RRM domain sequences, classified into 415 families. Whenever possible, the families are associated with the available literature and structural data. Moreover, the RRM families are organized into a network of sequence similarities that allows for the assessment of the evolutionary relationships between them.